2010
DOI: 10.1590/s0034-737x2010000600015
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de substratos e boro no enraizamento de estacas de pitaya

Abstract: Substrates and boron on the rooting of red pitaya cuttingsPitaya, a climbing fruit species belonging to the cactus family, has been largely commercialized in the Brazilian exotic fruit market. This study aimed to evaluate the effect of different substrates on the rooting of cladodes with the base immersed or not in boric acid solution. There was also evaluated the formation and initial development of roots, resulting in more vigorous, high-quality seedlings with higher survival rates. The experiment was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
2
3
0
1
Order By: Relevance
“…(Deshmukh et al 2019). Similar results were reported in dragon fruit (Santos et al 2010, Rahad et al 2016, Chahal 2020, lime cv Loomi (Abdullah and Al-Khateeb 2004), and pomegranate (Manila et al 2017, Deshmukh et al 2019 cuttings.…”
Section: Also Increase In Root Volumesupporting
confidence: 78%
“…(Deshmukh et al 2019). Similar results were reported in dragon fruit (Santos et al 2010, Rahad et al 2016, Chahal 2020, lime cv Loomi (Abdullah and Al-Khateeb 2004), and pomegranate (Manila et al 2017, Deshmukh et al 2019 cuttings.…”
Section: Also Increase In Root Volumesupporting
confidence: 78%
“…Galvão et al (2016), when analyzing plant growth in different substrates, concluded that soil and a mixture of sand and soil led to higher shoot fresh matter, shoot dry matter, and root dry matter, whereas sand resulted in higher root fresh matter. In line with these data, Santos et al (2010a) reported that washed sand led to higher root fresh matter and that substrates containing composted cattle manure (rich in organic matter) produced plants with higher shoot fresh matter.…”
Section: Irrigation Frequencysupporting
confidence: 66%
“…Cladodes (photosynthetic shoots) respond well to soil organic matter but develop extensive root systems in sand (Mizrahi & Nerd, 1999). Thus, a mixture of sand and a substrate rich in organic matter (such as composted cattle manure) is most suitable for obtaining strong, highquality plants from cuttings (Silva et al 2006;Santos et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Zinc can enhance rooting because it is involved in the biosynthesis of tryptophan, an auxin precursor (SCHWAMBACH et al, 2005). Boron, in turn, plays an important role in cell elongation and is considered a rooting cofactor, since it acts synergistically with endogenous auxin, facilitating its transport through the cell membranes (SANTOS et al, 2010;TAIZ and ZEIGER, 2013). These components taken together can explain the better performance for rooting and roots growth in P. actinia stem cuttings and also highlight the possibilities for using these extracts as alternative plant growth regulators.…”
Section: Resultsmentioning
confidence: 99%